Nitric Oxide-Mediated Regulation of Chitinase Activity and Cadmium Sequestration in the Response of Schizophyllum commune to Cadmium Stress - Dongxu Li; Chen Chu; Mengshi Zhao; Suying Hou; Rong Ji; Changhong Liu (Microorganisms)
Schizophyllum commune is an edible fungus with high medicinal value, but exposure to heavy-metal pollution poses significant health risks. Cadmium (Cd) toxicity inhibits fungal growth and leads to Cd accumulation in the mycelium. However, the regulatory mechanisms of Cd-induced growth inhibition and Cd accumulation remain poorly understood. Here, S. commune 20R-7-F01 was cultured in Cd-supplemented minimal medium (MM) to investigate the response of S. commune 20R-7-F01 to Cd exposure. We found that Cd exposure resulted in growth inhibition and a Cd-dependent increase in endogenous nitric oxide (NO) levels. NO production was primarily mediated by the nitrate reductase (NR) pathway. Cd-induced growth inhibition was alleviated by inhibiting NR activity or scavenging NO, highlighting the role of NO in stress responses. Furthermore, NO was found to enhance chitinase activity, thereby promoting Cd accumulation in the fungal cell wall and leading to growth inhibition. These results reveal a novel mechanism by which S. commune copes with Cd stress. This study highlights the potential of manipulating NO levels as a strategy to enhance fungal tolerance to heavy-metal pollution, providing a new avenue for managing environmental stresses in edible fungi and protecting human health.